Andbeyond : from Africa to India and beyond - Maunder, Peta Krost ([London] : SAGE, 2016)
Steven Fitzgerald looks relaxed as he arrives home from his fourth trip to South America this month. The chief executive officer of Andbeyond (originally Conservation Corporation Africa), a leader in luxury ecotourism, is taking his company to new climes. The company started in South Africa in 1990, spread its wings to other African countries and then ventured to India in 2004, where it had been successful - although with a few initial surprises. Now Fitzgerald has set his sights on South America. "Once you have seen lions, tigers in India are very enticing, as are jaguars, sloths and macaws in South America," he says. But, he asks himself, what have we learnt from opening in India that we can take with us to South America?
Originally Published in: Krost Maunder, P. (2009). Andbeyond: From Africa to India and beyond. WBS-2009-1. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; Tourism -- Planning -- Case studies